Peran Islamic Banking Digitalization terhadap Financial Inclusion dan Loyalitas Nasabah Muslim - Feri Hardiyanto; Agus Hidayat; Rudi Ferdiansah; Mohamad Maulana Ridzki (Cakrawala Repositori IMWI)
This study investigates the role of Islamic Banking Digitalization (IBD) on Financial Inclusion (FIN) and Customer Loyalty (LOY) among Muslim bank customers in West Java, with Customer Trust (TRUST) as a mediating variable. Employing a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach on 150 respondents selected through purposive sampling, results reveal that IBD (? = 0.312; p < 0.001), FIN (? = 0.278; p < 0.001), and their interaction IBD×FIN (? = 0.187; p = 0.003) positively and significantly affect customer loyalty. TRUST exerts the strongest direct effect on LOY (? = 0.423; p < 0.001) and partially mediates both IBD ? LOY and FIN ? LOY pathways (indirect ? = 0.167 and 0.144; p < 0.001). The model explains 68.47% variance in loyalty (R² = 0.6847). Findings underscore that Sharia-compliant digital banking services, integrated with financial inclusion strategies, are critical drivers of Muslim customer loyalty when underpinned by institutional trust and Islamic financial literacy.